1996
DOI: 10.1016/0014-5793(95)01460-8
|View full text |Cite
|
Sign up to set email alerts
|

Processing of pro‐islet amyloid polypeptide (proIAPP) by the prohormone convertase PC2

Abstract: Islet amyloid polypeptide (lAPP), 'amylin', is the component peptide of islet amyloid formed in Type 2 diabetes. IAPP is expressed in islet /]-cells and is derived from a larger precursor, proIAPP, by proteolysis. An in vitro translation/ translocation system was used to separately examine processing of human proIAPP by the/I-cell endopeptidases PC2, PC3 or furin. ProIAPP was converted to mature IAPP by PC2 but there was little conversion by furin or PC3. These data are consistent with processing of proIAPP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Therefore, in PC2 null mice, cleavage at the NH 2 -terminus is completely blocked (since only PC2 can cleave at this site) and cleavage at the COOH-terminus is mediated by PC1/3 and is normal, whereas in PC1/3 null mice, cleavage at the COOH-terminus is impaired (since PC1/3 preferentially cleaves at this site) but proIAPP is still processed to IAPP by the action of PC2 at both cleavage sites. These data are in agreement with earlier in vitro studies that suggested that PC2 can process proIAPP at its COOH-terminal cleavage site (30,31). Interestingly, the lack of active PC1/3 in PC1/3 Ϫ/Ϫ islets was not accompanied by a compensatory increase in PC2 protein levels, implying that normal levels of PC2 are enough to process proIAPP at both sites.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, in PC2 null mice, cleavage at the NH 2 -terminus is completely blocked (since only PC2 can cleave at this site) and cleavage at the COOH-terminus is mediated by PC1/3 and is normal, whereas in PC1/3 null mice, cleavage at the COOH-terminus is impaired (since PC1/3 preferentially cleaves at this site) but proIAPP is still processed to IAPP by the action of PC2 at both cleavage sites. These data are in agreement with earlier in vitro studies that suggested that PC2 can process proIAPP at its COOH-terminal cleavage site (30,31). Interestingly, the lack of active PC1/3 in PC1/3 Ϫ/Ϫ islets was not accompanied by a compensatory increase in PC2 protein levels, implying that normal levels of PC2 are enough to process proIAPP at both sites.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism(s) by which proIAPP, the IAPP precursor molecule, is processed in vivo is still not completely understood, but it is likely that the prohormone convertases PC1/3 and PC2, which are responsible for processing proinsulin to insulin and C-peptide (18,21,27,29), also mediate proIAPP processing (24,30,31). We have previously shown that mice lacking PC2 are unable to process proIAPP at its NH 2 -terminal cleavage site, indicating that PC2 is essential for proIAPP processing at the NH 2 -terminus in vivo (24).…”
Section: Discussionmentioning
confidence: 99%
“…This relative abundance of IAPP precursors might result from a combination of increased rates of synthesis (present data) and a saturation of the IAPP processing activity [21,23]. This would be expected to lead to the release of a higher proportion of precursor-and intermediate forms, similar to the relative hypersecretion of proinsulin from tissue with a higher proportion of this precursor [24].…”
Section: Discussionmentioning
confidence: 95%
“…This impairment in the initial step in proIAPP processing might be due to impaired action of PC3 in these mice, possibly because of substrate inhibition of the enzyme by the accumulation of the NH 2 -terminal proIAPP conversion intermediate. Alternatively, it is possible that PC2 may also contribute to processing of proIAPP at the COOH-terminal cleavage site, as has been suggested by in vitro studies (15,21).…”
Section: Discussionmentioning
confidence: 98%